Connecting Soft Power, Message Framing, and Political Actors’ Involvement in Online Media: The Case of ASEAN - Intentilia, Anak Agung Mia; Holzhacker, Ronald L. (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The research aims to examine media message framing in the selected Southeast Asia countries (Indonesia and the Philippines) surrounding events focusing on ASEAN’s 50th anniversary in 2017. The research explores the relations between media framing and ASEAN’s soft power, taking an interdisciplinary research approach combining political communication studies and international relations. The concept of soft power is divided into (a) strategic narrative and message framing and (b) state and non-state actors’ involvement in the communication process. The research uses qualitative content analysis and utilizes Atlas.ti software to conduct the coding process of online news items as the primary data. The main findings are as follows. First, ASEAN is portrayed with a rather positive tone on economic and socio-cultural issues. Second, ASEAN is portrayed on balance in a negative tone on political-security issues. Third, ASEAN state actors deliver more positive statements about ASEAN. Fourth, ASEAN non-state actors depict more negative statements about ASEAN. This research argues that positive news about economic and socio-cultural issues will likely enhance ASEAN’s soft power. On the other hand, communication with a negative tone about political-security issues may hinder the development of the institution’s soft power. ASEAN’s soft power is influenced by the communication of both state and non-state actors.